Video Edukasi Kontrasepsi Islami Dalam Meningkatkan Pengetahuan PUS Tentang Metode Kontrasepsi Islami Di PMB Nenden Kopo Bandung - Mochamad Salman Hasbyalloh; Niknik Nursifa; Hana Nurhanifah Budiadi (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2023)
Information on Islamic contraception in ripe-age couples is still extremely low. The number of couples of childbearing age who are unaware of the Islamic Family Planning (KB) method is influenced by a number of factors, including education. One technique that can give information to fruitful age couples is utilizing the Varying media Strategy Wellbeing. This study was conducted at the Midwifery Clinic